2009
DOI: 10.1007/s00267-009-9379-4
|View full text |Cite
|
Sign up to set email alerts
|

Conserving Mangrove Ecosystems in the Philippines: Transcending Disciplinary and Institutional Borders

Abstract: Humans are rapidly depleting critical ecosystems and the life support functions they provide, increasing the urgency of developing effective conservation tools. Using a case study of the conversion of mangrove ecosystems to shrimp aquaculture, this article describes an effort to develop a transdisciplinary, transinstitutional approach to conservation that simultaneously trains future generations of environmental problem solvers. We worked in close collaboration with academics, non-government organizations, loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 55 publications
0
34
0
2
Order By: Relevance
“…Local people have lived in mangrove areas for a long time, and in many cases, there is a mutual relationship between humans and their environment, including mangroves. Understanding and involving local wisdom in mangrove management has important implications for mangrovebased tourism management because of its role in defining active community support in mangrove conservation and local culture preservation [29,30]. Local wisdom is particularly important to increase the locality and uniqueness of local culture and tradition as part of the mangrove-based tourism attraction.…”
Section: Toward Sustainable Ecotourism In Mangrove Environmentsmentioning
confidence: 99%
“…Local people have lived in mangrove areas for a long time, and in many cases, there is a mutual relationship between humans and their environment, including mangroves. Understanding and involving local wisdom in mangrove management has important implications for mangrovebased tourism management because of its role in defining active community support in mangrove conservation and local culture preservation [29,30]. Local wisdom is particularly important to increase the locality and uniqueness of local culture and tradition as part of the mangrove-based tourism attraction.…”
Section: Toward Sustainable Ecotourism In Mangrove Environmentsmentioning
confidence: 99%
“…There are a lot of factors contributing to the success of bio-rights establishment in Pesantren Village including awareness on the importance of mangrove, calculation about threat of risk if mangrove does not exist (Sudtongkong and Webb 2008), recognition of potential benefits that would be obtained (Farley et al 2010) and support from all related stakeholder (Carter et al 2015). This success had made a change in the status of microcredit into pure grant which then can be utilized for developing further income generating activities.…”
Section: The Success Of Bio-rights Schemementioning
confidence: 99%
“…Jumnongsong et al (2015) found that the perception of potential benefits are more important for participation in mangrove management compared with the perception of threat and mangrove state. Subsequently, increasing awareness of the ecological and socio-economic importance of mangrove forests and other ecosystems, to balance these benefits against the benefits from conversion, and to change the mainstream development is extremely needed (Farley et al 2010). Above all, a social campaign meant to change attitude and increase of public awareness, active involvement and compliance with mangrove management programs of all related stakeholders especially coastal community in valuing the importance of mangrove ecosystem must occur.…”
Section: Perception On the Bio-rights Schemementioning
confidence: 99%
“…Hal serupa juga terjadi di Filipina dimana konservasi ekosistem mangrove yang melibatkan kelembagaan masyarakat lokal mampu mengembalikan fungsi mangrove secara optimal baik secara ekologi maupun ekonomi sehingga manfaat yang diperoleh (tangible maupun intangible) dalam jangka panjang jauh melebihi manfaat yang diperoleh jika mangrove dikonversi menjadi areal tambak udang intensif yang sebelumnya dianggap memberikan keuntungan sangat (Farley et al 2010). Hal ini menunjukkan bahwa dalam suatu pengembangan kegiatan, keberadaan kelembagaan yang mantap merupakan langkah awal bagi pertumbuhan ekonomi (Lutz 2011;Hall dan Ahmad 2013) serta peningkatan kesejahteraan masyarakat Hermanto dan Swastika (2011).…”
Section: Hasil Dan Pembahasan Dinamika Perkembangan Hutan Mangroveunclassified